Anti-inflammatory, antiangiogenic, and apoptosis-inducing activity of DLBS1442, a bioactive fraction of Phaleria macrocarpa, in a RL95-2 cell line as a molecular model of endometriosis - Tandrasasmita OM; Sutanto AM; Arifin PF; Tjandrawinata RR (Dove Medical Press, 2015)
Olivia M Tandrasasmita, Adeline M Sutanto, Poppy F Arifin, Raymond R Tjandrawinata Section of Molecular Pharmacology, Research Innovation and Invention, Dexa Laboratories of Biomolecular Sciences, PT Dexa Medica, Cikarang, West Java, Indonesia Abstract: DLBS1442 is a bioactive fraction extracted from the fruit of the native Indonesian plant, Phaleria macrocarpa (Scheff.) Boerl (Thymelaceae). This bioactive fraction is a potential treatment for dysmenorrhea and endometriosis. The present study investigated the pharmacological action of DLBS1442 in endometrial cells. The effect of various doses of DLBS1442 (0–200 µg/mL) over 24 hours was studied using the human endometrial RL95-2 cell line to observe its effect on angiogenesis, cell migration, estrogen and progesterone receptor levels, the eicosanoid pathway, cell viability, and apoptosis. The impact of DLBS1442 on nuclear factor kappa B (NFκB) and the eicosanoid pathway was also studied through its marker gene expression using a quantitative real-time polymerase chain reaction method. DLBS1442 showed an ability to inhibit angiogenesis and cell migration in a dose-dependent manner. At a dose of 100 µg/mL, DLBS1442 increased the cell population in sub-G1 phase from 7% to 34%. DLBS1442 also significantly downregulated the estrogen receptor level and upregulated the progesterone receptor level. Further, it inhibited the eicosanoid signaling pathway by reducing the NFκB transcription level and subsequent reduction of inducible nitric oxide synthase. A dose-dependent decrease in viability and increased apoptosis in RL95-2 cells were also evident after exposure to DLBS1442, where the IC50 was obtained at around 100 µg/mL. In conclusion, DLBS1442 is a potential agent for alleviating symptoms of endometriosis via its antiangiogenic, anti-inflammatory, and proapoptotic activity. Keywords: progesterone receptor, estrogen receptor, eicosanoid pathway, anti-inflammatory